Iranian women's experiences of breastfeeding support during the COVID-19 pandemic: A qualitative study - Parand Pourghane; Morvarid Ghasab Shirazi (Wolters Kluwer Medknow Publications, 2024)
Background: The impact of the coronavirus disease 2019 (COVID-19) pandemic on health systems worldwide has been associated with less attention to maternal support in breastfeeding. The objective of this study was to explore the experiences of breastfeeding mothers, during the COVID-19 pandemic, and the impact of the pandemic on breastfeeding initiation and maintenance. Materials and Methods: A qualitative, descriptive study was conducted by means of in-depth semi-structured interviews. The study participants included 28 mothers who had children aged 0 to 12 months, lived in Guilan Province, Iran, and had breastfed their children at least once after March 2021. Conventional content analysis was performed simultaneously with data collection. Results: Data analysis led to the extraction of three main categories and nine subcategories: in the shadow of peace (receiving correct information from reliable sources, observing health and quarantine principles, and enjoying the awareness of not having COVID-19 [both the mother and the infant]), under the stress (information poverty, invalid and stressful information, and stressful association of underlying diseases), and in the delusion of exposure (refusal to breastfeed, and non-compliance with recommendations). Conclusions: Mothers' breastfeeding experiences during the COVID-19 pandemic indicate factors such as receiving or not receiving breastfeeding support, quarantine and the resulting stress, and exposure to conflicting information. Mothers felt that their experience with breastfeeding during the pandemic encouraged them to continue breastfeeding, but it is important to support breastfeeding mothers. Monitoring and supporting vulnerable groups such as breastfeeding mothers, for mental health problems during the COVID-19 pandemic, should be considered during the planning phase.